QARAQALPAQSTAN RESPUBLIKASÍ SANAATÍNÍŃ RAWAJLANÍW TENDENCIYALARÍ - Yeshimbetov, U.X.; Abdiramanov, J.B.; Tolepov, E.T.; Genjemuratova, U.T. (SCIENCE and SOCIETY, 2026)
This article examines the regional characteristics of industrial development trends in the Republic of Karakalpakstan. The main focus of the article is on the dynamics of industrial growth, the share of industry in the creation of gross regional product, its share in Uzbekistan, and the growth dynamics of industrial sectors.